2015
DOI: 10.1007/s10899-015-9534-1
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Correlates and Morbidity in Lottery Gamblers: Results from a Population Survey

Abstract: The aim of the current study was to examine the socio-demographic correlates, the association of mental and physical illness, and the prevalence of pathological gambling among three groups (1) those with lottery gambling only (2) those with lottery and other types of gambling and (3) those with other types of gambling only-such as playing cards, sports betting, horse racing, casino gambling etc. Data was used from a nationwide cross-sectional epidemiological nationally representative survey of the resident (Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Of the three main activities examined, lottery was the only single, or exclusive, reported activity. These findings align with previous studies that have consistently demonstrated lottery gambling is popular and that many people gamble on this activity exclusively (Costes et al, 2018;Subramaniam et al, 2016). Because lottery gamblers are the majority of single-activity gamblers in this sample, it is perhaps unsurprising that fewer problem gamblers were observed in this group, as previous research has found that lottery gamblers are less likely to be problem gamblers (Subramaniam et al, 2016).…”
Section: Lotterysupporting
confidence: 91%
See 1 more Smart Citation
“…Of the three main activities examined, lottery was the only single, or exclusive, reported activity. These findings align with previous studies that have consistently demonstrated lottery gambling is popular and that many people gamble on this activity exclusively (Costes et al, 2018;Subramaniam et al, 2016). Because lottery gamblers are the majority of single-activity gamblers in this sample, it is perhaps unsurprising that fewer problem gamblers were observed in this group, as previous research has found that lottery gamblers are less likely to be problem gamblers (Subramaniam et al, 2016).…”
Section: Lotterysupporting
confidence: 91%
“…Binde (2011) reported that across problem gambling prevalence surveys, electronic gambling machines (EGMs), casino, Internet, and unregulated gambling were consistently the four forms of gambling found to be most strongly associated with problem gambling, whereas lotteries and instant lotteries were weakly associated. Research has also demonstrated that among exclusive lottery gamblers, the prevalence of problem gambling is significantly lower than that among non-exclusive lottery gamblers (Costes et al, 2018;Holtgraves, 2009;Subramaniam et al, 2016). In addition, it is well established that problem gamblers are more likely to engage in high-risk activities such as EGMs, whereas non-problem gamblers tend to participate in lowrisk activities such as lottery (e.g., Lund, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Using Icon Arrays to Communicate Gambling Information Reduces the Appeal of Scratch Card Games Lottery gambling is one of the most popular forms of legalized gambling (Ariyabuddhiphongs, 2011;Subramaniam et al, 2016;Welte et al, 2002). Within the category of lottery gambling are scratch card games, in which a gambler removes an opaque layer from a card with hopes of uncovering matching symbols corresponding to a prize.…”
mentioning
confidence: 99%
“…Although they are grouped together within the general category of lottery products, there is a considerable amount of heterogeneity in terms of structural characteristics within this group of products, particularly with regard to their potential for abuse or misuse. While a relatively high percentage of people report playing traditional lottery games (Ariyabuddhiphongs, 2011; Rogers, 1998), the potential for harm related to these draws is considered to be low (Subramaniam et al., 2016). One potential reason for this is the protracted event frequency associated with weekly lottery draws (the most common type of “draw” lottery), meaning that the time between the purchase of the lottery ticket and the outcome reveal is usually quite lengthy (e.g., on the order of days; Short, Penney, Mazmanian, & Jamieson, 2015).…”
Section: Introductionmentioning
confidence: 99%